Modelling and simulation of ephemeral streamflow in Ibadan, Nigera (2008)
" Flow variability of ephemeral rivers due to spatial and temporal distribution of rain fall and unregulated exploitation of water resources is a major cause of severe water supply shortages. With appropriate conservation planning of surface waste resources through hydrological modeling, timing of extraction of large volume without adverse effects on downstream requirement can be predicted. This study attempts to develop water balance components for evaluating flow characteristics essential for conservation planning of ephemeral streams. Daily meteorological data spanning 1973-2006, obtained from the International Institute of Tropical Agriculture, Ibadan weather station were used in developing predominant water balance model components of Ona Stream. Daily infiltration values were obtained using Crawford and Linsley’s model and interflow based on soil moisture levels. Data were statistically analyzed and developed models validated using 10 years meteorological data. Analyses showed that 93.4, 91.5 and 55.0 % variability in runoff was due to precipitation, groundwater storage and interflow respectively. Precipitation, interflow and groundwater storage were significant while evapotranspiration was insignificant (P.0.05) for runoff prediction. The water balance models simulated acceptable hydrologic processes such as interflow and groundwater storage which are generally difficult to measure directly. The R2 values obtained from validation range from 0.79 to 0.99. The water balance model thus improved the reliability of streamflow computation and other flow characteristics of the ephemeral Ona stream. It would appear that the ephemeral streamflow investigated depended more on the magnitude of precipitation interflow and groundwater flow while evapotranspiration (a major source of water loss in hydrologic water balance model) has relatively little effect on streamflow characteristics."